Innovative and Collaborative Strategies to Enhance the Competitiveness of MSMEs in the Digital Era - Putranto, Ardhi Setyo (Green Publisher Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) serve as a vital pillar in fostering inclusive and sustainable economic development across nations. Despite their significant contributions, MSMEs continue to face persistent challenges, including limited access to resources, bureaucratic constraints, and low innovation capacity. This study aims to identify key determinants enhancing MSME competitiveness in the digital era, focusing on entrepreneurial characteristics, public policy interventions, and the strategic use of digital technologies and social networks. This study employs an exploratory literature review approach to identify and examine key determinants that influence the competitiveness of MSMEs. The analysis focuses on several core dimensions: entrepreneurial characteristics, public policy interventions, and the strategic use of digital technologies and social networks. The findings highlight that adaptive strategic orientation, policy responsiveness to market dynamics, and the strengthening of cross-sector collaboration are critical drivers in enhancing MSME performance. Entrepreneurial traits like education, experience, and openness to innovation significantly influence competitiveness, while government support through regulatory simplification and digital infrastructure is essential. Additionally, leveraging social media and community networks enhances market access and resilience. These insights offer practical implications for stakeholders—particularly entrepreneurs and policymakers—in formulating more effective interventions to reinforce the role of MSMEs within the national economic framework.